A modalização como estratégia argumentativa em textos de vestibulandos - Andrade, Benedita Vieira de (2008)
In this work, the argumentative strategies construction in university entrance examinations texts is analyzed. The study intended to present, through the analyzed occurrences in the corpus, the discursive strategies use for the argumentation construction, observing the different lexicalization forms and the effects that these strategies produced for the intended meaning construction. Aiming to analyze the modalization via texts written by candidates for the UFRN entrance examination, the relations between this category and the resources used for the argumentative guidance of the text were highlighted. Conceived as a speaker argumentative strategy to express his/her relationship with the proposition content which enunciates, the modalization is, thus, one of the linguistic expression form used for the attainment of intended meaning effects in the argumentation construction. In order to substantiate the research, the theoretical assumptions adopted were the propositions which deal with this linguistic category, guiding it to a pragmatic-semantic perspective as well as a discursive-semantic one. Hence, Neves ( 1996, 2006), Koch ( 2000, 2002), Cervoni ( 1989), Bronkart (1999) and Castilho; Morais de Castilho (1996) studies, among others founded this work. Afterwards, a contextualized analysis of the modalized statements, taking into account all the set of elements implied on the argumentation construction, was carried out. The research, which had a strict qualitative character, revealed that the candidates make use of modalization to express commitment or dissociation as regards the statement which they produce; to obtain credibility and provide more authority to their arguments, thus avoiding them of being contested; to impose their arguments as real ones and acquire acceptance of the interlocutor; to lessen the proposition content and disguise the knowledge source; to comment the enunciation and attribute the discourse to another sender; to establish a dialogic relation with the interlocutor. In addition to offering support for new investigations, the research also aims to contribute for the mother tongue teaching, emphasizing the need of a focus which provides special attention to the written language functioning and its application diversity. In this work, the argumentative strategies construction in university entrance examinations texts is analyzed. The study intended to present, through the analyzed occurrences in the corpus, the discursive strategies use for the argumentation construction, observing the different lexicalization forms and the effects that these strategies produced for the intended meaning construction. Aiming to analyze the modalization via texts written by candidates for the UFRN entrance examination, the relations between this category and the resources used for the argumentative guidance of the text were highlighted. Conceived as a speaker argumentative strategy to express his/her relationship with the proposition content which enunciates, the modalization is, thus, one of the linguistic expression form used for the attainment of intended meaning effects in the argumentation construction. In order to substantiate the research, the theoretical assumptions adopted were the propositions which deal with this linguistic category, guiding it to a pragmatic-semantic perspective as well as a discursive-semantic one. Hence, Neves ( 1996, 2006), Koch ( 2000, 2002), Cervoni ( 1989), Bronkart (1999) and Castilho; Morais de Castilho (1996) studies, among others founded this work. Afterwards, a contextualized analysis of the modalized statements, taking into account all the set of elements implied on the argumentation construction, was carried out. The research, which had a strict qualitative character, revealed that the candidates make use of modalization to express commitment or dissociation as regards the statement which they produce; to obtain credibility and provide more authority to their arguments, thus avoiding them of being contested; to impose their arguments as real ones and acquire acceptance of the interlocutor; to lessen the proposition content and disguise the knowledge source; to comment the enunciation and attribute the discourse to another sender; to establish a dialogic relation with the interlocutor. In addition to offering support for new investigations, the research also aims to contribute for the mother tongue teaching, emphasizing the need of a focus which provides special attention to the written language functioning and its application diversity